Intra abdominal pressure changes in meshplasty and abdominal wall plication techniques in abdominoplasty: a comparative study - Pillai, Ramya Thulaseedharan; Joseph, Varghese; Marar, Krishnakumar (International Surgery Journal, 2021)
Background: Measurement of intra abdominal pressures is used to identify patients at risk of intra-abdominal hypertension and abdominal compartment syndrome after abdominoplasty that may lead to tight closure of the abdomen. This comparative study was aimed at measuring the IAP of patients in groups of meshplasty and abdominal wall plication, intraoperatively and post operatively. Methods: A comparative study was conducted among 34 patients who underwent meshplasty and abdominal wall plication. Each group comprised of 17 patients. All preoperative blood investigations and pre anesthetic evaluations were done. The technique used is decided based on the soft tissue laxity, rectus diastasis and presence of ventral hernias. Intra operatively, IAP was measured soon after the placement of mesh or after Rectus plication and post operatively, IAP was measured within 24 hours. IAP was measured using the intra vesical technique using Foley’s Catheter. Results: Fifty percent of the total patients were in the age group 41-50yrs and 88.2% of the patients were females. No significant variations in IAP, either intraoperative (p=0.051) or post operative (p=0.202), was evidenced in both groups. Post operatively, patient developed minimal complications such as seroma collection, wound infection and respiratory complications, improving on symptomatic treatment and antibiotics. Conclusions: No significant intraoperative or postoperative IAP was found between the two study groups underwent meshplasty and abdominal wall placation techniques.